2020
DOI: 10.1002/ppap.201900258
|View full text |Cite
|
Sign up to set email alerts
|

Plasma medical oncology: Immunological interpretation of head and neck squamous cell carcinoma

Abstract: The prognosis of patients suffering from advanced-stage head and neck squamous cell carcinoma (HNSCC) remains poor. Medical gas plasma therapy receives growing attention as a novel anticancer modality. Our recent prospective observational study on HNSCC patients suffering from contaminated tumor ulcerations without lasting remission after first-line anticancer therapy showed remarkable efficacy of gas plasma treatment, with the ulcerated tumor surface decreasing by up to 80%. However, tumor growth relapsed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 98 publications
0
21
0
Order By: Relevance
“…At sufficient concentrations, these species mediate oxidation-induced damage and death in tumor cells [7]. Plasma treatment was previously shown to control tumor growth in pre-clinical models effectively [10][11][12]. Moreover, first patients with tumors of the head and neck benefited from this new therapeutic approach and experienced a reduced tumor burden [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…At sufficient concentrations, these species mediate oxidation-induced damage and death in tumor cells [7]. Plasma treatment was previously shown to control tumor growth in pre-clinical models effectively [10][11][12]. Moreover, first patients with tumors of the head and neck benefited from this new therapeutic approach and experienced a reduced tumor burden [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Besides tumor toxicity, immunological aspects become increasingly important in cancer therapy 61,62 . Similar to other technology-driven therapeutics such as photodynamic therapy 63 , the role of plasma treatment as an adjuvant treatment to stimulate immunity was also previously proposed [64][65][66][67][68] and shown experimentally 24,67,[69][70][71] . This is needed as many types of tumors develop molecular strategies to evade immune-mediated attacks 72 .…”
Section: Discussionmentioning
confidence: 76%
“…In plasma medicine, oncology is a promising research field, and successful tumor reduction has already been observed in animal models and human patients suffering from endstage head and neck cancer [31,32]. Moreover, the exposure of cancer tissue to cold physical plasma was recently outlined to have an immunological dimension [33], but NK-cells have not been studied in the field of plasma medicine so far. To this end, we here investigated three human cell lines (two of malignant origin) and human peripheral blood-derived NK-cells to understand the immunomodulating consequences of plasma-treated skin cancer cells in co-culture with NK-cells Plasma-treated skin cancer cells augmented NK-cells-mediated tumor cell inactivation.…”
Section: Discussionmentioning
confidence: 99%